Análise dos polimorfismos Arg194Trp e Arg399Gln no gene de reparo de DNA XRCC1 em pacientes com meningite bacteriana - Pinheiro, Daniele Maria Lopes (2012)
Meningitis is a contagious infectious disease, in which it was shown that genetic characteristics are involved in disease susceptibility and inflammatory response and this can be determined by single nucleotide polymorphisms (SNPs). Reactive oxygen species (ROS) participates in the disruption of the blood brain barrier (BBB), thus contributing to the entry of the pathogen in the central nervous system (CNS), in which induces an inflammatory response, which has been associated with neuronal death and onset of sequels in patients who survive the disease. The base excision repair (BER) pathway is the main pathway involved in repair of oxidized DNA damage in neurons and has been implicated in response to bacterial meningitis (BM). This study evaluated two non-synonymous SNPs of repair gene XRCC1 Arg194Trp (rs 1799782) and Arg399Gln (rs 25487), in patients with bacterial meningitis (BM), and uninfected patients (control). The patient genotypes were investigated by PCR-RFLP. Genomics DNA damages were detected by formamidopyrimidine glycosylase (FPG) treatment. Immunoglobulins IgG and IgA were measured from plasma and cytokines and chemokines were quantified from cerebrospinal fluid samples. For the SNP XRCC1 Arg194Trp, we found no relation with the disease, however, was observed greater frequency of polymorphic alleles in XRCC1 Arg399Gln for control group compared to the group of patients with BM (P = 0,008; OR=0,45). No changes observed in cytokines levels, chemokines and immunoglobulins, as well as of DNA damage from patients with variant allele compared to patients with normal to the SNP allele XRCC1 Arg399Gln. In conclusion, it was seen an indication that the SNP in XRCC1 Arg399Gln has a possible protective effect against disease.